Implementation of Online Learning on PAI Subjects During the Covid-19 Pandemic (SYAMIL: Journal of Islamic Education, 2021)
The purpose of this study was to find out how the implementation of online learning was and the supporting and inhibiting factors in the implementation of online learning in PAI Subjects in the middle of the Covid-19 Pandemic eleventh (XI) grade science students. This study used a qualitative method. Sources of data used were primary data in interviews with school principals, PAI teachers, and students of class XI science and secondary data in the form of books, journals, scientific articles, the internet, and other scientific works. Data collection techniques were in the form of observation, interviews, and documentation. The data analysis technique used the model of Milles and Huberman, including data collection, data reduction, data presentation, and concluding the data obtained. The results showed that the implementation of online learning on PAI subjects in the middle of the covid-19 pandemic in class XI IPA started from government policy through SE Kemendikbud No. 4 of 2020 concerning the Implementation of Education Policies in the Emergency Period for the Spread of the Corona Virus. The implementation of this learning is based on the 2013 curriculum syllabus and uses online lesson plans (RPP). In the learning process, used Whatsapp, Youtube, and Schoology applications. The teacher also made various learning materials and media such as PowerPoint and videos related to the material. The process of learning evaluation was conducted by giving assignments or practice questions. The supporting and inhibiting factors for the implementation of online learning were able to be seen from three aspects, namely: (1) Human Resources (HR), (2) Materials or teaching materials, and (3) Supporting facilities.